2020
DOI: 10.2174/0929867325666180821151409
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Biomarkers for Tumor Angiogenesis: Where Are We?

Abstract: Numerous circulating biomarkers related to angiogenesis have been recently identified. Their use will allow identifying patients who are more likely to benefit from a specific anti-angiogenic treatment, as well as detecting those who will develop resistance and/or adverse effects. Nonetheless, further studies are required to elucidate the role of these biomarkers in clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 133 publications
0
5
0
Order By: Relevance
“…The detection of vascular phenotype and tumor cell genotype is still in the stage of preclinical research (Jubb et al 2006 ). Compared to using the tissue biomarkers to select effective anti-angiogenic drugs, the studies of discover and validation in the non-invasive, dynamic biomarker were at a more advanced stage, including measuring the circulating protein related to angiogenesis, circulating microRNAs, secrete body outside, circulating endothelial cells and or estimates of progenitor cells and vascular imaging (Paolo et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The detection of vascular phenotype and tumor cell genotype is still in the stage of preclinical research (Jubb et al 2006 ). Compared to using the tissue biomarkers to select effective anti-angiogenic drugs, the studies of discover and validation in the non-invasive, dynamic biomarker were at a more advanced stage, including measuring the circulating protein related to angiogenesis, circulating microRNAs, secrete body outside, circulating endothelial cells and or estimates of progenitor cells and vascular imaging (Paolo et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The detection of vascular phenotype and tumor cell genotype is still in the stage of preclinical research 34 . Compared to using the tissue biomarkers to select effective anti-angiogenic drugs, the studies of discover and validation in the non-invasive, dynamic biomarker were at a more advanced stage, including measuring the circulating protein related to angiogenesis, circulating micrornas, secrete body outside, circulating endothelial cells and or estimates of progenitor cells and vascular imaging 35 .…”
Section: Discussionmentioning
confidence: 99%
“…ANGPTL2 (angiopoietin-like protein 2) is a marker of angiogenesis [11], and it was significantly decreased by DHA treatment. Numerous studies have reported that angiogenesis is a hallmark of the malignant transformation of tumors [12, 13]. Several antitumor drugs are aimed at inhibiting neovascularization to reduce the oxygen and nutrient supply of tumors, which prevents the growth of tumors [1416].…”
Section: Discussionmentioning
confidence: 99%